Sittlich handeln als Zeugnis geben - Demmer, Klaus (Gregorianum, 1983)
The article attempts to shed light on one particular aspect of moral decision, which seems to be overlooked in present moral theological reflexion: i. e. the bearing witness to the underlying moral capacity of the believer's freedom. First of all attention is drawn to the epistemological framework, to the nature of moral insight and consequently to that of moral truth. Being based on the intuition of definite meaning of man's existence both are essentially linked to freedom. Moral truth is by its very nature free truth. And freedom in this proper context designates the inherent capacity of the will for the perceived moral good. There is a basic interdependence between goodness and rightness, which has to be protected by moral norms. This seems to be relevant for the process of weighing up what is good in concrete decision making. It is weighed up in the horizon of a precedent anthropological option and its correspondent understanding of human fulfillment. This takes place within the context of a permanent history of conflict. The moral subject strives to reach better alternatives of acting, which are capable of setting free from the constrictions immanent to human freedom. Moral truth is to be regarded as the result of a liberation process of both insight and freedom. Moral rightness implies a moral standard. It is precisely here that witnessing appears. Some further considerations are centered on the function of casuistry in so far as it denotes freedom combined with experience. They are followed by some clarifications as regards the much discussed issue of moral compromise in so far as moral judgment is concerned.